Factors Affecting the Quality of Life Among Pulmonary Tuberculosis Patients at the TB-DOTS Outpatient Clinic of Public Hospital - Zahra, Diandra Angelia Az; Sinaga, Bintang Yinke Magdalena (Public Health of Indonesia, 2024)
Background: Indonesia is the second country in the world with the highest burden of tuberculosis. Pulmonary tuberculosis is one of the global health issues that can substantially affect quality of life. Objective: To analyze the quality of life and associated factors among pulmonary tuberculosis patients. Methods: A cross-sectional study was conducted at the TB-DOTS outpatient clinic of Prof. Chairuddin Panusunan Lubis Universitas Sumatera Utara Hospital, Medan, Indonesia. The study subject was 100 pulmonary tuberculosis patients aged ≥18 years, newly diagnosed, and undergoing treatment from August to October 2023, selected using consecutive sampling. Primary data were collected through face-to-face interviews using the WHOQOL-BREF questionnaire. Descriptive statistics, the chi-square test, and the logistic regression test were used for data analyses. Results: The chi-square test showed there was a significant relationship between age (p = 0.022), family income (p = 0.005), treatment phase (p < 0.001), and adverse drug reactions (p = 0.040) with overall quality of life. The logistic regression test showed there was a significant relationship between family income (p = 0.007, OR = 3.685, 95% CI = 1.432–9.479) and treatment phase (p < 0.001, OR = 5.643, 95% CI = 2.139–14.888) with the deterioration of overall quality of life. Conclusion: The treatment phase lasting less than 2 months was the factor that most influenced the deterioration of the overall quality of life. Hence, families, healthcare workers, and the government should consider the treatment phase as a focus of interventions to enhance the quality of life of pulmonary tuberculosis patients